Desenvolvimento dos filhotes de atobas-de-pés-vermelhos (Sula sula) no aquipélego de Fernando de Noronha/PE - Rodrigues, Marcelo Câmara (2006)
Parental care s costs increase with the time spent due to incapacity of parents give assistance to increasing offspring food s requirement. This parental care deficits is crucial to offspring s emancipation that involve abilities development to they survive independently. In this work we observe 16 Red-footed boobies chick (Sula sula) on different stages of development, at area of Parque Nacional Marinho of Fernando de Noronha s archipelago, from August to October of 2005. Our data show the parents presence decrease during chick development and an activity frequency modification, in move and fly, which suggest the emancipation s chick development. We observe also the action of Kleptoparasits and the influence with offspring parental care. Our data show consistency with the literature. However, we consider that studies carried through during the peak of the reproductive station can support the hypothesis of that the conflicts, together with the initial period of development of the flight, can be representative in terms of mortality of chicks for the studied species